Fraud Risk in Peer Lending Fintech Transactions: The Role of Consumer Protection Regulation in Indonesia - Ratih Pratiwi; Muchammad Shidqon Prabowo; Marno Nugroho; Windi Novia Ratri Wardhani (International Journal of Social Science and Business, 2022)
Fintech P2P Lending has caused many complaints from its consumers. This study discusses how consumer protection regulations can reduce fraud from the P2P Lending platform. This study uses a normative research method using a legal approach and a case approach. The population used in this study were P2P customers. This study analyzes the problem with a legislative concerning consumer protection and financial services authority regulation about information technology borrowing and borrowing services. Data collection used primary legal materials in the form of laws and secondary legal materials obtained from library studies in the form of literature. The researcher applies a qualitative data analysis method. The results of this study are one of the key factors in protecting consumer rights derived from various regulations related to the supervision and supervision system carried out by the government. The government should do more education and outreach to the public regarding the fintech peer to peer lending platform and the formation of the Investment Alert Task Force. The study and formulation of government regulations must be balanced with the speed of technological change and digital transformation by involving practitioners so as not to harm each other. Synergy between stakeholders (collaboration), law, surveillance, and data protection can reduce the risk of illegal P2P platform practices. Coordination and synergy between policy makers and stakeholders will greatly facilitate handling in regulating the P2P Lending platform so as not to cause overlapping regulations that cause new problems.